Improved Pregnancy Outcome in Patients With Rheumatoid Arthritis Who Followed an Ideal Clinical Pathway. Issue 2 (1st February 2021) - Bortoluzzi, Alessandra; Andreoli, Laura; Carrara, Greta; Ramoni, Véronique; Rumi, Federica; Padovan, Melissa; Govoni, Marcello; Tincani, Angela; Scirè,; Carlo Alberto; ,
Abstract : Objective: To assess the effect of optimal management of pregnancy on a composite outcome of miscarriage and complicated birth among women with rheumatoid arthritis (RA). Methods: Data were extracted from health care databases of the Lombardy Region, Italy (2004–2013) as a part of the Record‐Linkage on Rheumatic Diseases Study. Analyses included women with RA identified through a copayment exemption code (International Classification of Diseases, Ninth Revision, Clinical Modification code 714.0) and controls from the general population, ages 18–50 years. Seven health care quality indicators (HCQI) were constructed and summarized in 3 pathway indicators: diagnostic, therapeutic, and prenatal follow‐up. Complicated birth or miscarriage were used to identify the adverse pregnancy outcome (APO). The relationship between HCQI and APO was analyzed using logistic models, and the results were presented as odds ratios (ORs) and 95% confidence intervals (95% CIs). Results: Data from the study cohort included the first pregnancy observed in 443 patients with RA compared with 6, 097 women belonging to the general population. In the RA population, patients who followed the 3 pathway indicators had a reduced risk of overall APO, with an OR of 0.60 (95% CI 0.39–0.94), and reduced risk of miscarriage/perinatal death, with an OR of 0.40 (95% CI 0.24–0.69), compared to those who did not follow the pathway indicators. Compared with the general population, patients with RA who met all HCQI during pregnancy displayed a risk of APO with an OR of 0.92 (95% CI 0.61–1.38) and miscarriage/perinatal death with an OR of 0.77 (95% CI 0.47–1.29). Conclusion: The adherence to an ideal clinical pathway of pregnancy management in women with RA restored the risk of APO to that expected for the general population.